PENERAPAN ARSITEKTUR KONTEKSTUAL DALAM PERANCANGAN KAWASAN WISATA BUDAYA SAMIN DI BLORA - Novitasari Rahayuningtyas; Trijoko Daryanto; Ofita Purwani (Universitas Sebelas Maret Surakarta, 2017)
Samin culture is one of the national heritage which is based on Samin’s tradition. The community of Samin is spread over some areas, one of them is Klopoduwur village, Blora. The uniqueness of Samin culture is the traditions, daily activities, and artifacts. Local government has decided to develope tourism in this village, which is reasonable in regard to its potentials. Tourism can help the economy of Samin people while at the same time induce its cultural activities. The Samin village, then, is designed by adding the tourism and culture facilities, also public infrastructures for the tourists and its society. Contextual architecture is applied in the design of the area, by applying visual elements to the old buildings and environment into the new buildings, to get the look which familiar for the Samin’s society, and also to get the authentic look for the tourists.Keywords: Samin culture, Contextual, Tourism, Visual continuity, Tradition